The Impact Of Palm Oil Plantations On Bird Diversity In Palm Oil Estates In Nagari Salareh Aia, Palembayan Sub-District, Agam District - Ismanto, Sahadi Didi; Nanda, Ririn Fatma (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2022)
This study aimed to see the effect of the existence of oil palm agricultural land on bird populations in the Agam area of West Sumatra Province. Observations were made directly by taking primary and secondary data.The species of birds that were identified during the observations were Pycnonotus goiaver (Merbah Cerocok) important value index 68.75 %, Streptopelia chinensis (Tekukur) IVI 42.50, Prinia familiaris (Prenjak Java) IVI 35.00 %, Colocalia esculenta (Cow Swallow) IVI 18.75 %, Copsychus saularis musicus (Murai) IVI 13.75 %, Halcyon smyrnensis (Javanese gecko) IVI 8.75 %, Rhipidura javanica (Stripe fan) IVI 6.25 % and Porzana cinerea (White Eyebrow Rat) with IVI 6.25%. The diversity of bird species in the oil palm plantations is low because only 8 bird species were found. The results of this study were basic data that need to be developed because there are effects that need to be multiplied further. The existence of oil palm plantations has an effect on the diversity of animal populations, especially birds around the land.